Family bereavement and organ donation in Spain: a mixed method, prospective cohort study protocol - David Rodríguez-Arias; Maria Victoria Martinez-Lopez; Elisabeth Coll; Francisco Cruz-Quintana; Beatriz Dominguez-Gil; Ivar R Hannikainen; Ramón Lara Rosales; Alicia Pérez-Blanco; Maria Nieves Perez-Marfil; Jose Miguel Pérez-Villares; David Uruñuela (BMJ Open, 2023)
Introduction There is a discrepancy in the literature as to whether authorising or refusing the recovery of organs for transplantation is of direct benefit to families in their subsequent grieving process. This study aims to explore the impact of the family interview to pose the option of posthumous donation and the decision to authorise or refuse organ recovery on the grieving process of potential donors’ relatives.Methods and analysis A protocol for mixed methods, prospective cohort longitudinal study is proposed. Researchers do not randomly assign participants to groups. Instead, participants are considered to belong to one of three groups based on factors related to their experiences at the hospital. In this regard, families in G1, G2 and G3 would be those who authorised organ donation, declined organ donation or were not asked about organ donation, respectively. Their grieving process is monitored at three points in time: 1 month after the patient’s death, when a semistructured interview focused on the lived experience during the donation process is carried out, 3 months and 9 months after the death. At the second and third time points, relatives’ grieving process is assessed using six psychometric tests: State-Trait Anxiety Inventory, Beck Depression Inventory-II, Inventory of Complicated Grief, The Impact of Event Scale: Revised, Posttraumatic Growth Inventory and Connor-Davidson Resilience Scale. Descriptive statistics (means, SDs and frequencies) are computed for each group and time point. Through a series of regression models, differences between groups in the evolution of bereavement are estimated. Additionally, qualitative analyses of the semistructured interviews are conducted using the ATLAS.ti software.Ethics and dissemination This study involves human participants and was approved by Comité Coordinador de Ética de la Investigación Biomédica de Andalucía (CCEIBA) ID:1052-N-21. The results will be disseminated at congresses and ordinary academic forums. Participants gave informed consent to participate in the study before taking part.